Parental involvement in safeguarding adolescent mental health: The importance of personality awareness - Taufiqurrahman, Ariz; Mahmud, Salami; Fadli, Fatmawati; Pranajaya, Syatria Adymas (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2026)
Adolescents (ages 10–19) face rising mental health challenges globally, including high rates of depression and anxiety. Research suggests that active parental involvement significantly improves adolescents psychological outcomes. For example, a recent meta-analysis found that treatments involving parents yielded better results than youth-only interventions. At the same time, stable personality traits influence adolescents’ vulnerability to mental health problems. High neuroticism predicts more depressive symptoms, whereas extraversion and conscientiousness often predict fewer depressive symptoms. However, the role of personality awareness—parents’ understanding of their adolescents’ individual personality profile—has been underexplored. This conceptual study employs a comprehensive literature review approach to explore the interrelated roles of parental engagement and sensitivity to adolescent personality in collaboratively supporting, promoting, and safeguarding the mental health and psychological well-being of adolescents. We find that (1) parental emotional support and authoritative parenting serve as protective factors; (2) many Indonesian youths report experiencing depression and desiring greater parental understanding; (3) personality-tailored support (e.g., recognizing a shy adolescent’s need for gentle communication) could improve outcomes; and (4) integrated programs involving parents in psychoeducation are recommended. These findings suggest that systematically training parents to recognize, understand, and respect their adolescents’ unique personalities significantly enhances the overall effectiveness and benefits of parental involvement. Concretely, community and school initiatives should include parent-focused components on adolescent personality and mental health. An empathetic parenting approach, based on knowledge of each adolescent's unique personality, can be a key element and important strategy for promoting adolescent well-being.